Intravenous Injections of Tissue Thromboplastin and Phospholipase C in Sheep - Carlsen, E; Hetland, Ø; Janson, T L (Thrombosis and Haemostasis, 1982)
To gain further information about the protective effect of phospholipase C (PLC) against intravascular coagulation, we have carried out studies in sheep. Thromboplastin infusions gave a dose-dependent increase in pulmonary platelet-bound 11 inactivity and a dose-dependent decrease in arterial oxygen tension, factor VIIIc activity, fibrinogen level and platelet count. All these parameters were significantly correlated when doses of 0.4 – 0.5 ml bovine thromboplastin/kg/min were given. The model therefore seemed suitable for testing the effect of PLC in preventing intravascular coagulation elicited by infusion of thromboplastin. Our experiments show that PLC may have a certain protective effect against pulmonary microembolism caused by thromboplastin infusion, but there was no normalization of the pulmonary 111In-radioactivity from labelled platelets, arterial oxygen tension, coagulation factors or platelet count in contrast to earlier observations in rats. Protection was observed against the effect of lethal doses of thromboplastin, but although small doses of PLC were used, both sheep eventually died of PLC toxicity.
Keywords: Factor VIII; Intravascular coagulation; Phospholipase C; Thromboplastin; Sheep